Natural disasters, growth and institutions: A tale of two earthquakes - Sauro Mocetti; Guglielmo Barone (European Regional Science Association (ERSA), 2013)
In this paper we examine the long-term impact of natural disasters using the synthetic control approach and, in contrast with the previous literature, a within country perspective. Therefore, we are able to better geographically define the area hit by the quake, to mitigate the role of unobserved confounders and use data that are much more comparable. We also examine the role of institutions in the reconstruction and we find that corruption and fraudulent behaviors flourish when local institutions are weak and amount of public transfers is huge.
Keywords: 330; earthquake; economic growth; institutions